MiR-192, miR-200c and miR-17 are fibroblast-mediated inhibitors of colorectal cancer invasion - Ast, Volker; Kordaß, Theresa; Oswald, Marcus; Kolte, Amol; Eisel, David; Osen, Wolfram; Eichmüller, Stefan B.; Berndt, Alexander; König, Rainer (OncoTarget, 2018)
mixed-integer linear programming; piecewise linear regression; extracellular matrix; tumor-associated fibroblast; tumor cell invasion